2021
DOI: 10.22616/esrd.2021.55.054
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Consumers’ Response to the Covid-19 Crisis in Latvia

Abstract: The regulations for restricting the Covid-19 virus set by the Latvian government, which entered into force on March 13, 2020, caused significant changes in the operation of outlets and consumer behavior. At the onset of the emergency, Latvia, like many parts of the world, experienced uncoordinated collective behavior that could potentially lead to significant changes in food supply chains. Therefore, one of the research directions of The National Research Program project “Towards the Post-pandemic Recovery: Ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Recent studies witness that people in Latvia, particularly during the COVID-19 pandemic, have started to pay more attention to their food consumption habits including healthy diets and locally produced food. People in Latvia have become more aware of food waste, food safety and the environmental impact related to the food production [42]. At the same time, consumers are visiting city markets and trade stands less and less (Figure 6).…”
Section: Brief Context In the Case Of Latviamentioning
confidence: 99%
“…Recent studies witness that people in Latvia, particularly during the COVID-19 pandemic, have started to pay more attention to their food consumption habits including healthy diets and locally produced food. People in Latvia have become more aware of food waste, food safety and the environmental impact related to the food production [42]. At the same time, consumers are visiting city markets and trade stands less and less (Figure 6).…”
Section: Brief Context In the Case Of Latviamentioning
confidence: 99%
“…Recent studies (e.g. CORDIS project..., 2016; Bite, Kruzmetra, 2021) show that there is a growing number of consumers who are aware of different types of impacts of the products they choose: where and how particular product was grown, produced and transported, what are impacts on their health, the environment and on animals. Local products play an important role in the daily diet of the population either they are purchased in small local markets, online or supermarkets; that is approved by several studies.…”
Section: Introductionmentioning
confidence: 99%
“…About one third of the respondents choose local products because they taste good (MAXIMA, 2020). Another study has indicated that people particularly during the Covid-19 pandemic have started to pay more attention to their eating habits, healthy diet and consumption of locally produced food products (Bite, Kruzmetra, 2021). Recently the neo-endogenous model or networked development (Lowe et at., 2019) gained greater academic interest as it anticipates specific needs of regions and local initiatives.…”
Section: Introductionmentioning
confidence: 99%